If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 * 5 + -6 = x Multiply 5 * 5 25 + -6 = x Combine like terms: 25 + -6 = 19 19 = x Solving 19 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 19 + -1x = x + -1x Combine like terms: x + -1x = 0 19 + -1x = 0 Add '-19' to each side of the equation. 19 + -19 + -1x = 0 + -19 Combine like terms: 19 + -19 = 0 0 + -1x = 0 + -19 -1x = 0 + -19 Combine like terms: 0 + -19 = -19 -1x = -19 Divide each side by '-1'. x = 19 Simplifying x = 19
| K+3K+32=27+2+5K | | 3y+3=-36 | | .50(3*2+68)=x | | 6(3*64-8*4)=x | | 12-3y=52+5 | | 5a=35 | | 29-x=13 | | r=-3 | | 17x-12=114+3x | | 5-7x=-15-3x | | -0.25y=16 | | x-2y+5=8 | | 8x^3+10x^2-5x-3=0 | | X+(-6)=9 | | -10p+9=12 | | 14c+35= | | 68-4*(3-1)3=c | | 6b+8= | | x^2+4bx+2b=0 | | X^3+2x^2-8x= | | 2x^12+3x= | | -3=5-t | | 173x+12=185 | | 173x+12=194 | | 173x+12=195 | | 3p-6= | | 173x+12=4278 | | 4b^2+7b+10=0 | | 4x^2-24x+100=0 | | 3q-40-4a=7a | | 3x+28=78 | | 3b-3=6(b+5) |